Vivências e convivências na Aldeia Caititu : um estudo acerca da situação sociolinguística da língua ancestral Manoki - Cruz, Adriana do Carmo Ribeiro de Souza (2021)
This paper presents the results of a sociolinguistic study carried out in the Manoki (Irantxe) indigenous community of the Caititu village, located in the Tirecatinga Indigenous Land, municipality of Sapezal, in the northwest region of Mato Grosso. The general objective of this research is to present a diagnosis of the sociolinguistic situation of the Caititu village, with the purpose of reflecting on the vitality of the ancestral native language and its strengthening in that community. To do this, we had as specific objectives: to conduct a historical survey of the Irantxe people (Manoki and Mỹky), highlighting the emergence of the Caititu village; to observe the linguistic coexistence in the community, presenting the sociolinguistic aspects observed, and to contribute with activities for the strengthening of the Manoki language in the Lino Araxi Irantxe Indigenous School. As a theoretical foundation, we used the contributions of Sociolinguistics, based on Calvet (2002), Edwards (1992), Hamel (1988), Labov (2008), Braggio (2002) and Pimentel da Silva (2009). The methodology used consisted of a bibliographic survey and then field research. In our experience with the indigenous people of the community, we applied interviews, collected statements, and made on-site observations. In the results, we present reflections allowed by the study, supported by the answers and statements of the interviewees, observed from the contexts of macro and micro variables, translating the feelings of enthusiasm in face of the process of retaking the remembrance of the ethnic language, its histories and culture.